CHARISMATIC LEADERSHIP OF KH. ALI WAFA ABDULLAH IN THE DEVELOPMENT OF ACCELERATION OF READING THE YELLOW BOOK IN PP. MAHFILUD DUROR II SUGER KIDUL JEMBER - Yaqin, Abdullah (Mozaic: Islamic Studies Journal, 2024)
Charismatic leadership emphasizes the existence of a special aura possessed by a leader which results in many followers who are loyal and obedient to him. A charismatic leader must continue to maintain his specialness towards his followers so that their obedience and obedience do not fade. The purpose of this study was to determine how the charismatic leadership of KH. Ali Wafa Abdullah and its impact on the development system of the acceleration program for reading yellow books at PP. Mahfilud Duror II. This study used a qualitative research approach with a case study type of research or commonly called case studies. The purposive sampling technique was used as the subject of the study. The data collection technique in this study used massive observation, interviews, and documentation, the results of which were analyzed using an idiosyncratic data analysis model. The validity of the data used was by triangulation of sources and triangulation of techniques. This study concluded that the management of the Islamic boarding school had implemented a modern managerial system by making the charismatic power of the Kiai a strengthener and driver of the management. The charismatic leadership of the Kiai also influences the managers of the yellow book reading acceleration program using the Prakom method to voluntarily and responsibly carry out the main tasks and functions both as managers and mentors.